Accelerated pre‐senile systemic amyloidosis in PACAP knockout mice: a protective role of PACAP in age‐related degenerative processes - Reglődi, Dóra; Longuespée, Rémi; Kriegsmann, Mark (The journal of pathology, 2018)
Dysregulation of neuropeptides may play an important role in aging‐induced impairments. Among them, pituitary adenylate cyclase‐activating polypeptide (PACAP) is a potent cytoprotective peptide that ...
First published: 17 May 2018
Gesehen am 12.12.2019